Perfil emergente del comunicador para las dinámicas actuales institucionalesen la provincia de El Oro. - Garcia Parrales, Angie Lisseth; Pua Arteaga, Ariana Michelle (Machala, 2021)
This research work is originated around changes and advances that have been evidenced in the institutional communication work, not only by the incursion of tools based on the use of Information and Communication Technologies (ICTs), but also by the processes that through them have been generated in the performance of communicational functions. Considered as the central nervous system of an organization, regardless of the sector in which its activities are developed (Márquez et al. (018), communication is the fundamental element when applying strategies, which is why it is essential that, as their environment presents changes, professionals has to adapt themselves to the field in which they will develop. This context has as result a redefinition of the profile of communication professionals, which produces the need for new knowledge, skills and abilities, in other words, communicators must be in constant training and knowledge acquisition that will allow them to progress as changes take place . Based on the above, the present study called Emerging communicator profile for current institutional dynamics in El Oro province", has as main objective to analyze the profile of the communicator to perform in the current dynamics of organizations in El Oro, and as specific objectives: a) Identify the work areas and functions assumed by communicators and managers in public and private institutions; b) determine the general and specific competencies and skills necessary to integrate institutional communication teams and c) evaluate profiles and challenges assumed by communicators to improve their performance in public and private institutions. To obtain the information that allowed to reach the objectives described, a mixed methodology was used with the application of quantitative and qualitative instruments, such as the application of interviews to professionals with 5 to 10 years of experience, who hold positions associated with the study subject; as well as interviews with experts with teaching and professional experience in the area; and finally a survey to graduates from the Social Communication Department of the Technical University of Machala (UTMACH). The results have been triangulated to reach final conclusions. Finally, respecting to the results obtained from the research instruments, it is found that there is no predetermined standard for institutional communicators since, as changes appear in the environment in which they perform their functions, it becomes necessary to acquire new knowledge, skills and abilities which, once acquired, will redefine the profile of the professional in question. Likewise, the preparation of this professional should not only remain stagnant in the basic knowledge of traditional journalism, but should be aware that the environment is evolving every day and with it the challenges to be assumed are becoming more complex and without the preparation and vocation he/she will not be able to fulfill them to the fullest, demonstrating that he/she is not a suitable professional for this area in the institution.
El presente trabajo de titulación se origina ante los diversos cambios y avances que se han evidenciado en el trabajo de la comunicación institucional, no solo por la incursión de herramientas basadas en el uso de las Tecnologías de la Información y la Comunicación (TICs), sino también por los procesos que a través de éstas han se han generado en el desempeño de las funciones comunicacionales. Al ser la comunicación, el sistema nervioso central de una organización, independientemente del sector en el que se desarrollen sus actividades, como señala Márquez et al. (2018) es el elemento fundamental a la hora de aplicar estrategias, motivo por el cual, es fundamental que conforme su entorno vaya presentando cambios estos profesionales se adapten al ámbito en el que se desenvolverá. Esto ha llevado a que el perfil de los profesionales en comunicación se vaya redefiniendo, por lo cual se produce la necesidad de obtener nuevos conocimientos, competencias y habilidades en otras palabras los comunicadores deben estar en constante capacitaciones y adquisición de conocimientos que les permitan progresar conforme se producen los cambios. A partir de lo descrito, el presente estudio denominado “Perfil emergente del comunicador para las dinámicas actuales institucionales en la provincia de El Oro”, tiene como objetivo principal analizar el perfil del comunicador para desempeñarse en las dinámicas organizacionales actuales en El Oro, y como objetivos específicos: a) identificar las áreas y funciones de trabajo asumidas por los comunicadores y responsables de comunicación en instituciones públicas y privadas; b) determinar las competencias y habilidades generales y específicas necesarias para integrar los equipos comunicación institucional y c) evaluar los perfiles y retos asumidos por los comunicadores para la mejora de su desempeño en las instituciones públicas y privadas. Para la obtención de la información que permitió cumplir con los objetivos descritos, se utilizó una metodología mixta con la aplicación de instrumentos cuantitativos como cualitativos, como la aplicación de entrevistas a profesionales de 5 a 10 años de experiencia, que desempeñan cargos asociados al tema de estudio; así como entrevistas a expertos con experiencia docente y profesional en el área; y una encuesta a graduados de la carrera de Comunicación Social de la Universidad Técnica de Machala (UTMACH), cuyos resultados han sido triangulados para llegar a las conclusiones finales. Por último, con respecto a los resultados obtenidos a partir de los instrumentos de investigación se constata que no existe un estándar predeterminado para los comunicadores institucionales puesto que, en virtud de cómo van apareciendo cambios en el entorno que desempeñan sus funciones se vuelve necesaria la adquisición de nuevos conocimientos, habilidades y destrezas mismas que una vez adquiridas redefinirá el perfil del profesional en cuestión. Asimismo, la preparación de dicho profesional no solo debe quedarse estancada en los conocimientos básicos del periodismo tradicional, debe ser consciente de que el entorno cada día va evolucionando y con ello los retos a asumir cada vez son más complejos que sin la preparación y vocación no podrá cumplirlos a cabalidad demostrando que no es un profesional apto para esta área en la institución.
Keywords: RELACION PUBLICA; SECTOR PUBLICO; PERIODISMO; TIC